2018
DOI: 10.1038/s41598-018-29183-2
|View full text |Cite
|
Sign up to set email alerts
|

Extract from Aphloia theiformis, an edible indigenous plant from Reunion Island, impairs Zika virus attachment to the host cell surface

Abstract: The mosquito-borne Zika virus (ZIKV) belongs to the flavivirus genus of the Flaviviridae family. Contemporary epidemic strains of ZIKV are associated with congenital malformations in infants, including microcephaly, as well as Guillain-Barré syndrome in adults. A risk of human-to-human transmission of ZIKV is also well documented. A worldwide research effort has been undertaken to identify safe and effective strategies to prevent or treat ZIKV infection. We show here that extract from Aphloia theiformis, an ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 43 publications
(45 reference statements)
3
63
0
Order By: Relevance
“…Medicinal plants have been used for millennia in the treatment and prevention against diseases and even until now, traditional medicine involving the use of herbal products are still widely practiced in Africa, Latin America, and China, and is gaining popularity in other countries including Australia and USA [80]. As the development of antivirals from synthetic molecules require a great amount of time and effort to design and validate from scratch, the discovery of antiviral compounds from natural products offers a more economical and simple alternative as they are easily accessible from nature [81][82][83]. Over the years, polyphenols-which are naturally occurring compounds found in fruits, vegetables, wine, and tea-have increasingly gained scientific interest as they have been reported to exhibit a wide range of pharmacological activities such as antiviral, anti-bacterial, antioxidant, anti-inflammatory, and anti-carcinogenic effects [84][85][86][87][88].…”
Section: Natural Products As a Source Of Antiviral Compoundsmentioning
confidence: 99%
“…Medicinal plants have been used for millennia in the treatment and prevention against diseases and even until now, traditional medicine involving the use of herbal products are still widely practiced in Africa, Latin America, and China, and is gaining popularity in other countries including Australia and USA [80]. As the development of antivirals from synthetic molecules require a great amount of time and effort to design and validate from scratch, the discovery of antiviral compounds from natural products offers a more economical and simple alternative as they are easily accessible from nature [81][82][83]. Over the years, polyphenols-which are naturally occurring compounds found in fruits, vegetables, wine, and tea-have increasingly gained scientific interest as they have been reported to exhibit a wide range of pharmacological activities such as antiviral, anti-bacterial, antioxidant, anti-inflammatory, and anti-carcinogenic effects [84][85][86][87][88].…”
Section: Natural Products As a Source Of Antiviral Compoundsmentioning
confidence: 99%
“…The recombinant Zika virus expressing the GFP reporter gene (ZIKV GFP ) and the clinical isolate PF-25013-18 of ZIKV-PF13 have been previously described [39,40]. The ZIKV progeny production was performed by measuring the quantity of infectious viral particles released into the supernatant by plaque-forming assay on vero cells, as previously described [23]. EGCG was purchased from Sigma-Aldrich.…”
Section: Cells Virus and Reagentsmentioning
confidence: 99%
“…Given that several countries around the world are at risk of ZIKV outbreaks, it is still of high importance to develop antiviral strategies that include the use of nutraceuticals that can be used to prevent ZIKV infection [17][18][19][20][21]. Several polyphenol-rich extracts from Reunion Island have been reported to prevent ZIKV infection in vitro [22][23][24][25]. The three natural compounds epigallocatechin gallate (EGCG), curcumin and delphinidin exert antiviral effects against ZIKV through a loss of viral infectivity in relation with an inability of virus particles to interact with host-cell receptors [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…This plant has been used in traditional medicine for the treatment of dysentery, malaria, fever [9], cataract, and diabetes [10]. Previous studies have also reported the antiviral [11], antidiabetic [12], antioxidant [9], antimicrobial [13], and photoprotective [8] activities of A. theiformis leaves. The active ingredient in this plant appears to be a xanthonoid class compound mangiferin.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have already investigated A. theiformis for its cytotoxicity, antiviral, antidiabetic, antioxidant activities, and chemical profile [11,16,17]. However to the best of our knowledge, systematic studies on the extraction, fractionation, and evaluation of A. theiformis antioxidant activity and composition of secondary metabolites have not been performed previously.…”
Section: Introductionmentioning
confidence: 99%